Salt bridges govern the structural heterogeneity of heme protein interactions and porphyrin networks: microperoxidase-11. Issue 56 (11th September 2020) - Porter, J.; Dit Fouque, K. Jeanne; Miksovska, J.; Fernandez-Lima, F.
Abstract : In this work, a proteolytic digest of cytochrome c (microperoxidase 11, MP-11) was used as a model to study the structural aspects of heme protein interactions and porphyrin networks. Abstract : In this work, a proteolytic digest of cytochrome c (microperoxidase 11, MP-11) was used as a model to study the structural aspects of heme protein interactions and porphyrin networks. The MP-11 structural heterogeneity was studied as a function of the starting pH ( e.g., pH 3.1–6.1) and concentration ( e.g., 1–50 μM) conditions and adduct coordination. Trapped ion mobility spectrometry coupled to mass spectrometry (TIMS-MS) showed the MP-11 structural dependence of the charge state distribution and molecular ion forms with the starting pH conditions. The singly charged ( e.g., [M] +, [M − 2H + NH4 ] +, [M − H + Na] + and [M − H + K] + ) and doubly charged ( e.g., [M + H] 2+, [M − H + NH4 ] 2+, [M + Na] 2+ and [M + K] 2+ ) molecular ion forms were observed for all solvent conditions, although the structural heterogeneity ( e.g., number of mobility bands) significantly varied with the pH value and ion form. The MP-11 dimer formation as a model for heme-protein protein interactions showed that dimer formation is favored toward more neutral pH and favored when assisted by salt bridges ( e.g., NH4 +, Na + and K + vs. H + ). Inspection of the dimer mobility profiles (2+ and 3+ charge states) showed a high degree of structural heterogeneity as a function of the solution pH and ion form; the observation of common mobility bands suggest that the different salt bridges can stabilize similar structural motifs. In addition, the salt bridge influence on the MP-11 dimer formations was measured using collision induced dissociation and showed a strong dependence with the type of salt bridge ( i.e., a CE50 of 10.0, 11.5, 11.8 and 13.0 eV was observed for [2M + H] 3+, [2M − H + NH4 ] 3+, [2M + Na] 3+ and [2M + K] 3+, respectively). Measurements of the dimer equilibrium constant showed that the salt bridge interactions increase the binding strength of the dimeric species.